Influence of shoe drop on running kinematics and kinetics in female runners - Besson, T.; Morio, C.; Millet, G. Y.; Rossi, J. (European Journal of Sport Science, 2019)
This study investigated the effects of shoe drop on lower limb kinematics and kinetics in female runners.